Cholinergic Basal Forebrain Volumes Predict Gait Decline in Parkinson's Disease. Issue 3 (31st December 2020) - Wilson, Joanna; Yarnall, Alison J.; Craig, Chesney E.; Galna, Brook; Lord, Sue; Morris, Rosie; Lawson, Rachael A.; Alcock, Lisa; Duncan, Gordon W.; Khoo, Tien K.; O'Brien, John T.; Burn, David J.; et al.
ABSTRACT: Background: Gait disturbance is an early, disabling feature of Parkinson's disease (PD) that is typically refractory to dopaminergic medication. The cortical cholinergic system, originating in the nucleus basalis of Meynert of the basal forebrain, has been implicated. However, it is not known if degeneration in this region relates to a worsening of disease‐specific gait impairment. Objective: To evaluate associations between sub‐regional cholinergic basal forebrain volumes and longitudinal progression of gait impairment in PD. Methods: 99 PD participants and 47 control participants completed gait assessments via an instrumented walkway during 2 minutes of continuous walking, at baseline and for up to 3 years, from which 16 spatiotemporal characteristics were derived. Sub‐regional cholinergic basal forebrain volumes were measured at baseline via MRI and a regional map derived from post‐mortem histology. Univariate analyses evaluated cross‐sectional associations between sub‐regional volumes and gait. Linear mixed‐effects models assessed whether volumes predicted longitudinal gait changes. Results: There were no cross‐sectional, age‐independent relationships between sub‐regional volumes and gait. However, nucleus basalis of Meynert volumes predicted longitudinal gait changes unique to PD. Specifically, smaller nucleus basalis of Meynert volume predicted increasing step time variability ( P = 0.019) and shortening swing time ( P = 0.015); smaller posterior nucleus portions predicted shortening step length ( P = 0.007) and increasing step time variability ( P = 0.041). Conclusions: This is the first study to demonstrate that degeneration of the cortical cholinergic system predicts longitudinal progression of gait impairments in PD. Measures of this degeneration may therefore provide a novel biomarker for identifying future mobility loss and falls. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society. Abstract : March Infographic: Cholinergic Basal Forebrain Volumes Predict Gait Decline in Parkinson's Disease